The importance of green education in primary, secondary and higher education: A review - Adnyana, I Made Dwi Mertha; Mahendra, Kadek Adi; Raza, Syed Meesam (Journal of Environment and Sustainability Education, 2023)
This review aimed to provide an understanding of the importance of implementing green education in primary, secondary, and higher education. Green education is important in primary, secondary, and higher education because it promotes environmental conservation and sustainability. It integrates various disciplines and fosters ecological awareness, responsible citizenship, and sustainable practices. Green education in primary education introduces basic environmental concepts, whereas secondary education delves deeper into environmental issues and emphasizes critical thinking. Higher education provides specialized programs and courses in environmental studies, sustainability science, and green technology, equipping students with the expertise necessary to address global environmental challenges. Green education facilitates evidence-based learning, enabling individuals to make informed decisions and take action toward a more sustainable world.